Effects of chalcone derivatives on players of the immune system - Lee JS; Bukhari SNA; Fauzi NM (Dove Medical Press, 2015)
Jian Sian Lee, Syed Nasir Abbas Bukhari, Norsyahida Mohd Fauzi Drug and Herbal Research Center, Faculty of Pharmacy, Universiti Kebangsaan Malaysia, Kuala Lumpur, Malaysia Abstract: The immune system is the defense mechanism in living organisms that protects against the invasion of foreign materials, microorganisms, and pathogens. It involves multiple organs and tissues in human body, such as lymph nodes, spleen, and mucosa-associated lymphoid tissues. However, the execution of immune activities depends on a number of specific cell types, such as B cells, T cells, macrophages, and granulocytes, which provide various immune responses against pathogens. In addition to normal physiological functions, abnormal proliferation, migration, and differentiation of these cells (in response to various chemical stimuli produced by invading pathogens) have been associated with several pathological disorders. The unwanted conditions related to these cells have made them prominent targets in the development of new therapeutic interventions against various pathological implications, such as atherosclerosis and autoimmune diseases. Chalcone derivatives exhibit a broad spectrum of pharmacological activities, such as immunomodulation, as well as anti-inflammatory, anticancer, antiviral, and antimicrobial properties. Many studies have been conducted to determine their inhibitory or stimulatory activities in immune cells, and the findings are of significance to provide a new direction for subsequent research. This review highlights the effects of chalcone derivatives in different types of immune cells. Keywords: macrophages, neutrophils, T-cells